2019
DOI: 10.1111/ele.13331
|View full text |Cite
|
Sign up to set email alerts
|

Flowers respond to pollinator sound within minutes by increasing nectar sugar concentration

Abstract: Can plants sense natural airborne sounds and respond to them rapidly? We show that Oenothera drummondii flowers, exposed to playback sound of a flying bee or to synthetic sound signals at similar frequencies, produce sweeter nectar within 3 min, potentially increasing the chances of cross pollination. We found that the flowers vibrated mechanically in response to these sounds, suggesting a plausible mechanism where the flower serves as an auditory sensory organ. Both the vibration and the nectar response were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 79 publications
1
74
0
3
Order By: Relevance
“…For instance, the plant Solanum lycopersicum releases its pollen only in the presence of a particular vibration of the air caused by pollinating insects (Torres‐Ruiz & Jones, 2012). Also, Oenothera drummondii flowers produce a more sugary nectar after exposure to playback of the natural sound of bee wingbeats (Veits et al, 2019). These authors observed that petals vibrate when they receive a specific sound, and hypothesized that flowers can be considered as sense organs.…”
Section: Flowers Nectar and Fertilizationmentioning
confidence: 99%
“…For instance, the plant Solanum lycopersicum releases its pollen only in the presence of a particular vibration of the air caused by pollinating insects (Torres‐Ruiz & Jones, 2012). Also, Oenothera drummondii flowers produce a more sugary nectar after exposure to playback of the natural sound of bee wingbeats (Veits et al, 2019). These authors observed that petals vibrate when they receive a specific sound, and hypothesized that flowers can be considered as sense organs.…”
Section: Flowers Nectar and Fertilizationmentioning
confidence: 99%
“…Many animals, including herbivores and their predators, respond to sound [22][23][24]. Recently, plants were also demonstrated to respond to sounds [13,[25][26][27][28], e.g., by changing gene expression of specific genes [26,27], or by producing sweeter nectar in response to pollinator 20 sound [28]. If plants are capable of emitting informative airborne sounds, these sounds have a potential for triggering a rapid effect on nearby organisms, including both animals and plants.…”
Section: Introductionmentioning
confidence: 99%
“…If we accept that there is a physical layer of communication in the soil, how can we study it? This requires a methodological retooling that will not be straightforward, since capturing, recording, and replaying relevant sounds in an acoustically insulated environment at the scale required is a challenge [3,16]. One of the potential challenges is sound attenuation in porous media, which has been studied in the context of localizing buried objects [17].…”
Section: Approaches For Studying Soundmentioning
confidence: 99%